2021
DOI: 10.1101/2021.02.04.429714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional classes of SNPs related to psychiatric disorders and behavioral traits contrast with those related to neurological disorders

Abstract: We investigated the functional classes of genomic regions containing SNPS contributing most to the SNP-heritability of important psychiatric and neurological disorders and behavioral traits, as determined from recent genome-wide association studies. We employed linkage-disequilibrium score regression with several brain-specific genomic annotations not previously used. The classes of genomic annotations conferring substantial SNP-heritability for the psychiatric disorders and behavioral traits differed systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…This fact was first noted in the landmark study of schizophrenia by the Schizophrenia Working Group of the Psychiatric Genomics Consortium (2014) and found repeatedly since. Recent work has shown that the genetics of behavioral and psychiatric traits are in this way clearly distinguishable from genetic liabilities for neurological disorders, for which more of the heritability lies in coding regions ( Reimers and Kendler, 2022 ).…”
Section: Genes Mental Illness and Resiliencementioning
confidence: 99%
“…This fact was first noted in the landmark study of schizophrenia by the Schizophrenia Working Group of the Psychiatric Genomics Consortium (2014) and found repeatedly since. Recent work has shown that the genetics of behavioral and psychiatric traits are in this way clearly distinguishable from genetic liabilities for neurological disorders, for which more of the heritability lies in coding regions ( Reimers and Kendler, 2022 ).…”
Section: Genes Mental Illness and Resiliencementioning
confidence: 99%